A descriptive survey on the manifestation of family centeredness in the furniture placement of the living room spaces of selected Filipino extended families - Tupaz, Karen T.; Faustino, Johanna Acab. (2010.)
ABSTRACT This study involved an observation of the living room spaces of low to middle income Filipino extended families in search of the manifestation on the value of family-centeredness as reflected in their interior layouts. Using a purposive sampling, extended Filipino families were chosen based on their monthly income ranging from P10,000 to P50,000 and through the families' household size which should be greater than five (5). A mutli-method research including interviews, personal observations and photo documentation was conducted for the data collection which lasted for (5) five consecutive days in selected areas in Metro Manila. The manifestation of Filipino value of family-centeredness was observed based on the types of activities performed by the extended families in their living spaces. Group and individual activities by each respondent family were studied in relation to the way the furniture pieces were arranged in the living areas of the respondent families. Results showed that the value of family-centeredness was manifested on the furniture placement of the living rooms of the ten respondent families. Due to the lack of space, the furniture pieces in the living areas of the respondent families were likewise used for individual activities. Group activities on the other hand, help promote family bonding for the extended families. Based on the data gathered, the placement of furniture pieces in the living rooms of the ten respondents were more effective for group activities rather than for individual activities. Further studies regarding the topic on family-centeredness in other areas of the home is recommended which may be helpful in designing Filipino spaces in the future.
Thesis (B.S. Interior Design)--University of the Philippines Diliman.
Keywords: Living rooms -- Philippines -- Interior decoration; Living room furniture